Friedman's money supply rule vs optimal interest rate policy - George W. Evans; Seppo Honkapohja (Bank of Finland, 2003)
Using New Keynesian models, we compare Friedman's k-percent money supply rule to optimal interest rate setting, with respect to determinacy, stability under learning and optimality.We first review the recent literature.Open-loop interest rate rules are subject to indeterminacy and instability problems, but a properly chosen expectations-based rule yields determinacy and stability under learning, and implements optimal policy.We then show that Friedman's rule also can generate equilibria that are determinate and stable under learning.However, in computing the mean quadratic welfare loss, we find that for calibrated models Friedman's rule performs poorly compared to the optimal interest rate rule.
URN:NBN:fi:bof-20140807326
Keywords: E52; E31; 330; monetary policy; determinacy; stability under learning